Restructuring Top Management: Evidence from Corporate Spinoffs - Wruck, Eric G.; Wruck, Karen H. (Journal of Labor Economics, 2002)
We examine corporate spinoffs as events through which top management is restructured. Our main findings are: (1) firm‐specific human capital and human capital, in the form of governance expertise and top management experience, affect the composition of spinoff firms’ top management; (2) spinoff top management structure is related to the value created by a spinoff; and (3), for a subsample of firms, spinoffs serve as a form of management dismissal, with the opportunity to manage a smaller, weaker spinoff firm serving as a “consolation prize.”